Applying the Principles of Nuremberg in the International Criminal Court - Philippe Kirsch (Washington University Global Studies Law Review, 2007)
The Nuremberg trials constituted a historic moment in the development of international law. They were important in their own right as a response to the atrocities of the Second World War. At the same time, they gave rise to a new system of international criminal justice. This system includes national courts, ad hoc international and mixed tribunals, and now the International Criminal Court (“ICC”). All of these institutions are rooted in Nuremberg.
Keywords: War crimes; Nuremberg War Crime Trials; Nuremberg; Germany; 1945-1949; International criminal law; International offenses; Procedure (Law); Right to fair and impartial trial